Propuesta de Caracterización y alternativas de mejora de la cadena de suministro para la producción del banano en el departamento del Magdalena (2024)
The banana is an important fruit product marketed worldwide; in Colombia it is ranked among the top 10 agricultural products exported to different countries, five varieties of bananas are cultivated: Dominico, Dominico Hartón, Hartón, Cachaco or Popocho, and Pelipita. Of the total cultivated area in the country, only 13% is dedicated to technified banana monoculture (DANE, 2022).